Pathogenic deep intronic PCSK1 variant causes proprotein convertase 1/3 deficiency in a family: short report - Huber, Leah M.; Subaşıoğlu, Aslı; Garczarczyk-Asim, Dorota; Valovka, Taras; Müller, Thomas; Adam, Rüdiger; Janecke, Andreas R. (Clinical genetics, 2025)
Proprotein convertase 1/3 (PC1/3), encoded by PCSK1, is expressed in neuronal and endocrine cell types, where it activates a number of protein precursors that play roles in energy homeostasis. Biallelic PCSK1 loss-of-function mutations cause a polyendocrinopathy; a total of 34 patients were reported. An infant with congenital malabsorptive diarrhea of all carbohydrates underwent exome sequencing (ES), with particular consideration of PC1/3 deficiency, but no mutations were found. The onset of obesity in the second year of life increased suspicion of PC1/3 deficiency in the proband, as well as in his equally affected cousin. Transcript analysis revealed minor amounts of an aberrant PCSK1 transcript containing intron 9 sequence and encoding a premature stop codon (p.Pro400Valfs*35). A deep intronic PCSK1 variant, NG_021161.1(NM_000439.5):c.1196+2681T>A, was found to segregate in the proband's family with the disease. A minigene approach demonstrated that the identified deep-intronic variant underlies pseudo-exon inclusion of the intron 9 sequence in the transcript. The characteristic phenotype of PC1/3 deficiency might require extended genetic testing to make a timely diagnosis.